Improving system reliability of HF RFID reader and comparison between different antennas for tv applications - Türksever, Nuray. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Developments in Radio frequency identiﬁcation (RFID) technology in the recent history, has increased signiﬁcantly. With such developments and improvements RFID technology provides many advantages. RFID allows none-LOS and contactless opera tions to be done, it has features such as, multiple tag identiﬁcation, long read range and tag re-programmability. With the increased usage of the smarts phones, the need and the demand for the RFID technology has also increased in the area of consumer applications. In this thesis, design steps of a 13.56 MHz RFID reader and antenna that used in a RFID TV application has examined, performance comparisons between diﬀerent types and sizes of antennas has been made aiming to get the most accurate and reliable system with determining the best reader antenna geometry. By examining the results, it has seen that optimum return loss and impedance have been achieved in all types of antennas. Additionally, the best antenna geometry and size has been observed for RFID TV application. On the other hand, results of the experiments also show that metal proximity which is caused by the metal shieldings of TV unit and capacitance eﬀect of the passive card have signiﬁcant eﬀects on the return loss and the read range.
Keywords: Radio frequency identification systems.; Multimedia systems.